Longitudinal Analysis of the Milwaukee County Child Care Subsidy Program: 1996-2001 - (:unkn) unknown (My University, 2002)
Milwaukee County requested that the Employment and Training Institute for administrative purposes report on patterns of use for families participating in child care subsidy programs to assist the county in its long-term efforts to build an effective child care delivery system for employed families. Expenditures and participation levels are detailed by a variety of demographic characteristics including age and number of children, income levels, transportation status, type of care, length of time during which subsidized care is provided, and public assistance participation status.
Keywords: child care; welfare policy; child poverty